2013
DOI: 10.5539/jas.v5n9p143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Bio Fertilizers on Growth and Yield of Canola (Brassica napus L) var RGS 003

Abstract: Bio fertilizers effects were studied on growth and yield of canola in Sistan and Balochistan province. An experiment was conducted in a randomized complete block design with three replications. Treatments included bio-fertilizers at eight levels (not inoculation, phosphate bio-fertilizer (barvar2), Nitro Kara, Bio sulfur, phosphate bio-fertilizer (barvar2) +Nitro Kara, Nitro Kara+ Bio sulfur, phosphate bio-fertilizer (barvar2) + Bio sulfur and phosphate bio-fertilizer (barvar2) + Nitro Kara + Bio sulfur). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
4
3
0
Order By: Relevance
“…The use of bio-fertilizers resulted in a considerably larger number of branches/plant (11.71), which aids in the release of growth stimulating compounds, resulting in enhanced root development, water transportation, nutrient absorption, and breakdown. The current findings are also consistent with those of Mahboobeh and Jahanfar [8]. Phosphorous also plays an important function as a structural component of cell constituents and metabolically active molecules such as chloroplasts, mitochondria, phyton, nucleic acid, protein, flavin nucleotides, and many enzymes.…”
Section: Growth Parameterssupporting
confidence: 92%
“…The use of bio-fertilizers resulted in a considerably larger number of branches/plant (11.71), which aids in the release of growth stimulating compounds, resulting in enhanced root development, water transportation, nutrient absorption, and breakdown. The current findings are also consistent with those of Mahboobeh and Jahanfar [8]. Phosphorous also plays an important function as a structural component of cell constituents and metabolically active molecules such as chloroplasts, mitochondria, phyton, nucleic acid, protein, flavin nucleotides, and many enzymes.…”
Section: Growth Parameterssupporting
confidence: 92%
“…There is speculation it may be related with the properties of high electrical conductivity and transmittance, and chemical stability and large bandgap (Rani et al, 2002). Further, the positive impact of TNPs on seedlings was found in present study, which agrees with findings in radish, corn, lettuce, cucumber (Lin and Xing, 2007), canola (Mahmoodzadeh et al, 2013) and wheat plant (Jaberzadeh et al, 2013) due to the improvement of antioxidant activities. And it was also reported that TNPs may help Cuminum cyminum L. against drought stress as increase of leaf prolin, which is in membrane structures and scavenges ROS under water deficiency (Salajegheh et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…With bio-sulfur fertilizer, the maximum number of silique seeds per plant could be generated for canola plants. Also, with a nitrogen biofertilizer, bio-sulfur can lead to the highest yield for grapes [5].…”
Section: Introductionmentioning
confidence: 99%